Discovery of thiazolidin-4-one urea analogues as novel multikinase inhibitors that potently inhibit FLT3 and VEGFR2. Issue 10 (15th May 2019) - Qi, Baohui; Xu, Xingwei; Yang, Ying; Zhou, Yuting; Chen, Tao; Gong, Guowei; Yue, Xupeng; Xu, Xin; Hu, Liping; He, Huan
Graphical abstract: Highlights: Novel thiazolidin-4-one urea analogues were designed and synthesized. 17b was identified as a FLT3/VEGFR2 dual inhibitor. 17b induced cytotoxicity and suppression of migration, antiproliferation, apoptosis. Abstract: A series of novel thiazolidine-4-one urea analogues were designed, synthesized and biologically evaluated. The structure-activity relationship (SAR) at several positions of the scaffolds was investigated and its binding mode was analyzed by molecular modeling studies. Compound17b proved to be the most potent one, and IC50 values against A549 and HT-29 cancer cell lines were 0.65 μM and 0.11 μM, respectively. The results of kinase profile demonstrated that compound17b is a multikinase inhibitor that potently inhibits FLT3 (IC50 = 8.6 nM) and VEGFR2 (IC50 = 18.7 nM). The results of real-time live-cell imaging indicated that compound17b showed excellent cytotoxicity and anti-proliferative activity against HT-29 cancer cells in a time- and dose-dependent manner, which was significantly potent than that of Cabozantinib. In addition, in vitro antitumor activity was associated with inducing cancer cell apoptosis and suppression of cancer cell migration.